Immediate implant placement in molar extraction sites: a 1-year prospective case series pilot study - Henny J. A. Meijer; Gerry M. Raghoebar (SpringerOpen, 2020)
Abstract Background There is a growing tendency to place single tooth implants immediately after extracting a failing tooth in the posterior region. The aim of this prospective case series pilot study was to evaluate immediate implant placement in molar post-extraction sites during a 1-year follow-up period. Materials and methods Fifteen consecutive patients with a single failing molar in the maxilla or mandible, and presenting enough bone to expect primary implant stability and an implant site free of infection, were included. The implants, with a large thread depth and sharp thread edges, were placed in each patient according to a two-staged surgical procedure. Three months later, a full contour screw-retained zirconia restoration with an angulated screw channel abutment was provided. Clinical and radiographic examinations were performed 1 month and 12 months after placing the restoration. In addition, the patients' satisfaction with the restoration was scored after 12 months. Results Four out of 15 of the mobile implants had to be removed before the 1-year evaluation. The implant and restoration survival rates were 73.3% at the 1-year evaluation (n = 15). The mean marginal bone loss, from loading to the 12-month follow-up, was 0.17 mm (n = 11). The mean plaque, calculus, peri-implant mucosa, bleeding, and pocket probing depth scores were low, depicting healthy peri-implant conditions. The patients were very satisfied. Conclusion It was demonstrated, within the limitations of this study, that immediate placement of regular diameter implants in molar post-extraction sites in the maxilla and mandible resulted in a high implant failure rate during a 1-year follow-up period. Trial registration Netherlands Trial Register, NL8117. Registered 24 October 2019 - Retrospectively registered, https://www.trialregister.nl/trial/8117.